2013
DOI: 10.1002/term.1697
|View full text |Cite
|
Sign up to set email alerts
|

Vascular tissue engineering of small-diameter blood vessels: reviewing the electrospinning approach

Abstract: Vascular tissue engineering is a relevant research field aimed at elaborating and proposing innovative solutions to overcome the drawbacks related to the use of conventional blood vessel substitutes, especially referring to small-diameter grafts. For this aim, electrospinning can be regarded as a valuable technique to produce novel scaffolds with several functional characteristics that can be usefully tailored for the application discussed here. The reproduction of the natural extracellular matrix obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 127 publications
1
84
0
1
Order By: Relevance
“…Burst strength demonstrating the ability of the vascular graft to withstand pressure was estimated as 2633 ± 383 mm Hg which is higher than the acceptable value. This is because the clinical efficacy of vein grafts is approximately 2000 mm Hg, which is justified as an acceptable minimum criterion for burst strength …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burst strength demonstrating the ability of the vascular graft to withstand pressure was estimated as 2633 ± 383 mm Hg which is higher than the acceptable value. This is because the clinical efficacy of vein grafts is approximately 2000 mm Hg, which is justified as an acceptable minimum criterion for burst strength …”
Section: Discussionmentioning
confidence: 99%
“…This is because the clinical efficacy of vein grafts is approximately 2000 mm Hg, which is justified as an acceptable minimum criterion for burst strength. 24,55 Sufficient amount of suture retention is also essential to successfully implant a vascular graft. Ideally, suture retention of vascular grafts should fall within the ranges reported for gold standards of vascular bypass including saphenous vein and internal mammary artery.…”
mentioning
confidence: 99%
“…It has been previously reported that SDF-1a promotes neovascularization, cardiogenesis, and tissues repair by recruiting endogenous stem/progenitor cells and by influencing the development of monocytes toward a pro-tissue formation phenotype. [32][33][34] Biocompatibility assessment of vascular grafts showed enhanced cellularization and tissue regeneration in SDF-1 and SDF-1/heparin groups compared with the control group 4 weeks after implantation. This is attributed to the SDF-1a, which can enhance endogenous cell mobilization.…”
Section: Discussionmentioning
confidence: 96%
“…Although vascular grafts composed of expanded polytetrafluoroethylene (ePTFE) or polyethyleneterephthalate (Dacron) are already used in the replacement of large-or mediumdiameter vessels, these materials are not suitable for small-diameter vessels because of thrombosis and intimal hyperplasia [43,44] . According to Ercolani et al, the optimal small-diameter vascular graft should have mechanical strength, biocompatibility, an acceptable healing response, and ease of handling [45] . Electrospinning has become an effective technique for the production of small-diameter vascular grafts because these grafts mimic the natural extracellular matrix with a high surface area, high porosity, and small pores.…”
Section: Vascular Tissue Engineeringmentioning
confidence: 99%